Identifikasi kecacatan produk menggunakan Lean Six Sigma melalui pendekatan konsep DMAIC - Muh Yazid Gandi; Asep Erik Nugraha; Apid Hapid Maksum; Billy Nugraha (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2022)
Lean Six Sigma has been known as part of a method for identifying the defects of a product. One approach is the DMAIC Concept, namely Define, Measure, Analyze, Improve and Control. It is to be oriented that it will be known the average product is defective and needs to be done the act of improvement. So the purpose of this study is to find out the type of product defects in the form of dolls, carpets and mattresses. The scientific was result in one just for Doll Industries locating at North Cikampek Village, Karawang Regency. Result from scientific, have 5 (five) categories of product defects in the form of: untidy stitching, uneven doll stuffing, wrinkle dolls, materials that are not environmentally friendly and colors are not appropriate. At the Define stage, problem identification, goal determination, process objectives and improvements are carried out. In the Measure stage, crtitical to quality (CTQ) measurements are taken. At the Analyze stage, a cause-and-effect analysis is performed. In the Improvement stage, the analysis of 5W+1H is carried out. At the Control stage, continuous improvement control is carried out.